Ethnobotanical Studies in the Ritual of Panjang Jimat Ceremony at the Kasepuhan Palace Cirebon - Jabar, Muhammad Abdul; Falah, Bagus Hammam; Andini, Putri Imas; Kartika, Ema (Universitas Muhammadiyah Yogyakarta, 2024)
Indonesia is the second country with a high level of biodiversity and culture from each region. One area that has high biodiversity and culture is the city of Cirebon. The unique culture of Cirebon City which combines aspects of biodiversity and culture is the Panjang Jimat Ritual which is carried out at the Kasepuhan Palace in Cirebon. This ritual is carried out on the night of 12 Rabiul Awwal which aims to commemorate the birthday of the Prophet Muhammad SAW. However, until now, there has been no research that examines the various types of plants used in this ceremony, even though knowledge of the types of plants used can help to determine the status of natural resources, the distribution of plants, and the interactions between plants and people in the city of Cirebon. Therefore, this study aims to identify various types of plants and their symbolic meanings used in the Panjang Jimat ritual. The research method used is descriptive quantitative by collecting data through interviews and observation. The results showed that there were 18 plants used in this ceremony which included Oryza sativa, Cocos nucifera, Rosa sp., Mangifera indica, Musa paradisiaca, Magnolia alba, Curcuma longa, Syzygium aromaticum, Zingiber officinale, Cinnamomum verum, Jasminum sambac, Styrax japonica, Cananga odorata, Citrus sp., Bambusa sp., Arenga pinnata, Salacca zalacca, and Malus sp. This research is the first time it has been conducted, so ethnobotanical studies are very important to determine the interaction between plants and the local people of Cirebon.